Board games to improve the speaking skill in students of tenth grade basic year at escuela de educación básica 11 de Diciembre No.4. La Libertad, province of Santa Elena, school year 2015-2016. - Villamar Tomalá, Jessica (2016)
The present research paper was focused on the improvement of the speaking skill through the application of board games. This project was carried out with a qualitative approach and it was applied with phenomenological aspects and study cases for getting a better understanding of teaching-learning situations with students. In this case, the difficulties presented in the institution are related to the deficiency of material resources and the application of traditional methods that are usually applied in the classroom. On the other hand, the tools and techniques applied for collecting essential data were the interviews, observation and review of documents. Therefore, this research allowed comprehending that the use of board games were an effective support in the improvement of speaking skill. So, the playful activities permit the interaction and cooperation between students and avoid in this way boring classes. As a result, they will be practical as educational strategies to learn for the reason that when students play they enjoy and learn more easily.